Law Enforcement on Merger of Indemnity Claims in Criminal Case Persecution - Edi Sutomo (Law Development Journal, 2020)
The purpose of this study is to analyze and explain: the causes of the Crime of Persecution; Implementation of Law Enforcement on the Merger of Indemnity Claims in the Criminal Case of Persecution, the factors that hinder the implementation of the Law Enforcement, as well as the efforts made in overcoming the obstacles in the Merger of Indemnity Claims in the Criminal Case of Persecution at the Sampang District Court in the future. This type of research is normative legal research supported by empirical legal research, and uses a statutory approach as primary legal material. The results showed that the causes of the crime of persecution in Sampang Regency were: alcohol and psychological factors. Implementation of Law Enforcement on the Merger of Indemnity Claims in the Criminal Case of Persecution at the Sampang District Court, it is known that the defendant has been tried with criminal sanctions, but does not include compensation for victims of criminal acts of persecution. Obstacles or barriers to the implementation of law enforcement on the merger of indemnity suit in the case of criminal offense at the Sampang District Court are: the legal factor itself; law enforcement factors; factor of means or facilities that support law enforcement; community factors; cultural factors.